A case report and case review: Chronic myeloid leukemia (CML) blast phase with myelomastocytic differentiation. (2020) - Song, Jinming; Liu, Kenian; Pinilla-Ibarz, Javier; Zhang, Hailing
Abstract: We presented a patient with CML who progressed to unclassical blast phase after Tyrosine Kinase Inhibitors (TKIs) therapy. The patient presented with 2 populations of blasts: one with no cytoplasmic granules and was CD117 weak+/tryptase-/CD34- (typical myeloblasts), and another with metochromatic granules in the cytoplasm and was CD117 strong+/tryptase+/CD25+/CD34 subset+ (myelomastocytic blasts). Almost all the cells were positive for BCR/ABL1 fusion and no KT V816F mutation was detected. The patient was misdiagnosed as having blast phase CML with coexisting mast cell leukemia at an outside institute. Three similar cases and previously described myelomastocytic leukemia are reviewed and discussed.